ANALISIS PENGEMBANGAN METODE ENTER-EXIT DALAM PROGRAM MENGHAFAL AL-QUR’AN (TELAAH TEORI STRUKTURAL FUNGSIOANL TALCOTT PARSONS) - Iffatul Aimmah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
Al-Qur'an memorization activities are gaining more and more space in many institutions, however not a few students feel afraid to memorize the Al-Qur'an. At JQH IDIA a method has been implemented that is expected to answer this fear, namely the Enter-Exit method. The research method used is a qualitative approach with the process of collecting data through observation, interviews and documentation. The results of the study revealed that the foundation of the enter-exit method is the qaul of Imam Nawawi. The application of the enter-exit method uses functionalist structural: 1)The adaptation of the method was carried out on Islamic teachings, JQH and IDIA. 2) Goal Attainment is carried out by formulating four method objectives 3)The integration of methods is created from the role of each functionary and the creation of solidarity among members. 4) Latencies is carried out by maintaining things that are in accordance with the JQH IDIA environment Keywords: Exit-enter method, JQH memorization program, functional structural theory